2020
DOI: 10.25273/pe.v10i2.6801
|View full text |Cite
|
Sign up to set email alerts
|

From face-to-face learning to web base learning: How are student readiness?

Abstract: <p align="justify">Learning readiness influences learning success. Changing the learning model requires preparation. Well-planned online learning is different from learning in an emergency. This study aims to determine the readiness of student learning in online learning during the Covid-19 pandemic. The type of research used non-experimental quantitative. The data collection method is done by survey. Data analysis uses descriptive statistics. The subjects in this study were PGSD students at Mataram Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
21

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 22 publications
4
50
0
21
Order By: Relevance
“…This section discusses the literature examining the effect of the pandemic on higher education, including challenges and benefits of online learning and students' readiness for the sudden shift to that mode of learning. The majority of studies explored undergraduate students (Adnan & Anwar, 2020;Jeffery & Bauer, 2020;Mishra et al, 2020), with only some focusing on postgraduate ones (Patricia Aguilera-Hermida, 2020; Widodo et al, 2020). Some studies found that students preferred face-to-face classes over online ones (Adnan & Anwar, 2020;Patricia Aguilera-Hermida, 2020), while others found that online classes were favoured over traditional face-to-face ones (Mishra et al, 2020;Paudel, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This section discusses the literature examining the effect of the pandemic on higher education, including challenges and benefits of online learning and students' readiness for the sudden shift to that mode of learning. The majority of studies explored undergraduate students (Adnan & Anwar, 2020;Jeffery & Bauer, 2020;Mishra et al, 2020), with only some focusing on postgraduate ones (Patricia Aguilera-Hermida, 2020; Widodo et al, 2020). Some studies found that students preferred face-to-face classes over online ones (Adnan & Anwar, 2020;Patricia Aguilera-Hermida, 2020), while others found that online classes were favoured over traditional face-to-face ones (Mishra et al, 2020;Paudel, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Patricia Aguilera-Hermida (2020) found that students preferred face-to-face classes over online ones and that technical difficulties were reported to be one challenge experienced by students. A study by Widodo et al (2020) discovered that the majority of students could not learn properly in the online mode of learning due to technical difficulties, high costs, and lack of training. Adnan and Anwar (2020) discovered that students were mostly dissatisfied with online learning and preferred face-to-face interaction due to the high cost and lack of Internet connection for most people in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot be denied that online learning activities have many negative impacts [23]. Students' unpreparedness in adjusting to online learning has various negative impacts [24]. Therefore, a campaign is needed to carry out sports activities for students.…”
Section: Manipulative Movementmentioning
confidence: 99%
“…Penggunaan metode daring dalam keadaan tertentu lebih efektif jika dibandingkan dengan tatap muka (Widodo, Nursaptini, et al 2020). Salah satu manfaatnya adalah agar para peserta pelatihan lebih siap pada saat pendampingan penulisan PTK.…”
Section: Hasilunclassified